SEMINAR PENINGKATAN KESADARAN HUKUM PADA REMAJA SISWA SMK NEGERI 2 MAKASSAR - Amrah, Nurmaya; Zainuddin, Kurniati; Nurdin, Muh. Nur Hidayat; Maya, Maya; Kadir, Almanda Meidynita; Mentari, Fardatillah Nur; Alfriani, Alfriani (LPPM Institut Pendidikan Nusantara Global, 2022)
This activity aims to increase legal knowledge and awareness for teenagers through engaging seminars with the theme